Gʹyu thog sñiṅ thig bla sgrub kyi drag poʼi Sbyin sreg rta rṅams ʼbar ba bźugs so - Khams-smyon Dharma-seṅge (s.n., 1973)
Ritual for the raudrahoma in the practice of the rites of the Gʹyu thog sñiṅ thig.